2015
DOI: 10.1111/ajad.12182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of injectable extended‐release naltrexone (XR‐NTX) for opioid dependence on residential rehabilitation outcomes and early follow‐up

Abstract: XR-NTX may be an effective adjunct in the residential treatment and aftercare of patients with opioid dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…(6466) However, limited data are available on the safety and efficacy of naltrexone during pregnancy. (67, 68)…”
Section: Medication-assisted Therapymentioning
confidence: 99%
“…(6466) However, limited data are available on the safety and efficacy of naltrexone during pregnancy. (67, 68)…”
Section: Medication-assisted Therapymentioning
confidence: 99%
“…However, there is limited experience with this drug medication outside specialized treatment settings. XR‐NTX has frequently been offered to patients who have completed extended residential treatment15 and to patients for whom initiation of relapse‐prevention treatment with XR‐NTX was relatively uncomplicated because of current abstinence 16. Most patients in need of treatment, however, are actively using opioids at the time of initial evaluation and require completion of opioid withdrawal before XR‐NTX initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is growing interest in XR-NTX treatment among OUD populations, particularly among daily heroin users (Ahamad, et al, 2015). Leslie, et al (2015) found that patients who received an initial injection of XR-NTX while in a residential setting had lower rates of AMA discharge and higher rates of transition to outpatient care than those who did not receive XR-NTX. Notably, in that study of persons leaving residential care, first appointment follow-up rates for continuing care in the first 10 days post-discharge were also low.…”
Section: 0 Discussionmentioning
confidence: 97%
“…Leslie, et al found that those who received XR-NTX while in residential treatment were less likely to leave against medical advice (AMA) and more likely to engage in follow-up care post-discharge than those who did not receive XR-NTX (Leslie, et al, 2015). …”
Section: 0 Introductionmentioning
confidence: 99%